Improving Students’ Writing Skill in Recount Text using Team Games Tournament - Farisa Rahma Yulita; Armeria Wijaya; Listya Dewi Damajanti (PROCEEDING UMSURABAYA, 2026)
This study aims to improve the recount text writing skills of eighth-grade students at SMP Negeri 34 Surabaya in the academic year of 2024/2025 through the implementation of the Team Games Tournament (TGT) strategy. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using observation sheets and tests in the form of pre-test and post-test. The results revealed an improvement in students’ average scores from 70.00 (pre-test) to 78.70 in Cycle I, and further to 83.54 in Cycle II. The mastery level also increased from 58.06% to 87.10%. In addition to academic improvement, students showed high enthusiasm, active participation, and positive engagement throughout the learning process. Therefore, the TGT strategy proved to be effective in enhancing students' writing skills in recount texts and is recommended as an alternative teaching approach for writing instruction in junior high school English classes.